2000
DOI: 10.1046/j.1365-2605.2000.00223.x
|View full text |Cite
|
Sign up to set email alerts
|

Proteasomes in human spermatozoa

Abstract: In the present study we describe the localization of proteasomes in human spermatozoa by means of immunolabelling with different monoclonal and polyclonal antibodies detected by confocal microscopy. Western blotting confirmed the specificity of the antibodies and has shown that proteasomes are present in spermatozoa and in seminal fluid. In spermatozoa proteasomes are concentrated in the neck region where the centrioles are located. Some labelling was also detected at the periphery of the head, but no proteaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
2
3

Year Published

2002
2002
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 53 publications
2
35
2
3
Order By: Relevance
“…Although some discrepancies across species are reported, all studies report an implication of proteasome in events related to the acrosomal reaction (Morales et al 2003, Sutovsky et al 2004, Rawe et al 2008. Proteasomes have also been detected at the connecting piece between head and tail in bovine and human sperm (Wojcik et al 2000, Rawe et al 2008. It has been suggested that they play different roles during the post-fertilisation disassembly of the sperm tail connecting piece, sperm aster formation, pronuclear development and apposition (Rawe et al 2008).…”
Section: Proteomic Comparison Of Sperm Proteins From Bullsmentioning
confidence: 99%
“…Although some discrepancies across species are reported, all studies report an implication of proteasome in events related to the acrosomal reaction (Morales et al 2003, Sutovsky et al 2004, Rawe et al 2008. Proteasomes have also been detected at the connecting piece between head and tail in bovine and human sperm (Wojcik et al 2000, Rawe et al 2008. It has been suggested that they play different roles during the post-fertilisation disassembly of the sperm tail connecting piece, sperm aster formation, pronuclear development and apposition (Rawe et al 2008).…”
Section: Proteomic Comparison Of Sperm Proteins From Bullsmentioning
confidence: 99%
“…data). Proteasomal subunits were also detected inside or near the sperm centriole (Bialy et al, 2001;Mochida et al, 2000;Wojcik et al, 2000). These could be either an inactive carryover of dismantled proteasomes and ubiquitinated centrosomal proteins or a part of the proteolytic apparatus that could be activated and instrumental in the release of the sperm centriole at fertilization.…”
Section: Ubiquitin In Spermatogenesismentioning
confidence: 99%
“…Ubiquitin (Fig. 1L) and the 26 S proteasomal-subunits localize to the centriolar region of the sperm tail (Wojcik et al, 2000) and to the other parts of the sperm tail midpiece (Mochida et al, 2000), and may be instrumental in this process. Fol- lowing the sperm aster formation, S-phase, and pronuclear apposition, the first embryonic mitosis is controlled by the ubiquitin-dependent degradation of cyclin B, a recurring component of the maturation promoting factor (Josefsberg et al, 2001).…”
Section: Fertilization Mitochondrial Inheritance and Early Embryonimentioning
confidence: 99%
See 1 more Smart Citation
“…Sawada et al (1998) and(2002) proposed that the main component of the vitelline coat that exhibits sperm receptors was in fact multiubiquitinated and then degraded by the sperm ubiquitin-proteasome pathway during ascidian fertilization. Interestingly, multiple proteasomal subunits have been detected in the sperm acrosomes of various mammalian species including human, boar, bull, rat and mouse spermatozoa (Baker et al 2008a, b;Baska et al 2008;Biały et al 2001;Morales et al 2003Morales et al , 2004Sutovsky et al 2004;Wojcik et al 2000;Ziemba et al 2002). Additionally, multiple ubiquitin-specific proteases (Baker et al 2008a, b) and the ubiquitin conjugating enzyme E2 (Fischer et al 2005;Sutovsky et al 2000) have also been identified in the proteomes of mammalian spermatozoa.…”
Section: Proteasomes In Sperm-oocyte Interactionsmentioning
confidence: 99%